How is the composition of wastewater affected by variations in the environment? - A characterisation of organic matter, nitrogen, and phosphorus in the influent wastewater at Rya wastewater treatment plant in Gothenburg - Rehnberg, Frida (My University, 2021)
More stringent future demands on effluent wastewater quality, together with changes in precipitation patterns due to climate change, make it increasingly important to understand how the composition of wastewater can be affected by environmental parameters. Organic matter, nitrogen, and phosphorus are the main pollutants wastewater treatment plants are built to remove. To ensure efficient removal, it is essential to know more about the speciation of these compounds. This study characterised the influent wastewater at Rya wastewater treatment plant in Gothenburg, mainly focusing on organic matter, but also including nitrogen and phosphorus in the analysis. The aim was to identify how the composition of wastewater is affected by external factors such as precipitation, water temperature, infiltration and inflow, and design of the sewer system (i.e. combined or separate sewers). The total COD concentration in the influent wastewater ranged between 310 – 620 mg COD/L during the sampling period. Approximately 85% was particulate COD, where 45% was slowly degradable COD, 31% inert particulate COD and 9% heterotrophic biomass. The colloidal COD corresponded to around 6%. Approximately 15% was defined as soluble COD, with 8% inert soluble and 7% readily degradable COD. The readily degradable COD consisted of 2% acetate and 5% other readily degradable COD. The results were compared with previous characterisations and variations in the results were discussed. Precipitation diluted the wastewater and caused a decrease in the concentrations of soluble fractions of organic matter, nitrogen, and phosphorus in the water. However, the particulate fractions increased with increased precipitation, probably since particles were transported with the infiltration and inflow. Gothenburg has a large share of combined sewers, which carry both stormwater and wastewater to the wastewater treatment plant. The results were, therefore, compared to a previous wastewater characterisation conducted in Linköping, which has a large share of separate sewers, to identify the impact of infiltration and inflow on the composition of the influent wastewater. Low volumes of infiltration and inflow found in separate sewers seem to result in lower concentrations of soluble inert organic matter and increasing concentrations of slowly degradable organic matter. Results from this study show that there are soluble fractions of nitrogen and phosphorus that are not removed to the same extent as other fractions in the treatment process but could be important to look into further with the increasing demands on treatment in the future. Current CHALMERS Architecture and Civil Engineering, Master’s Thesis ACEX30 III characterisations focus on fractioning organic matter, but future studies should include nitrogen and phosphorus to increase the knowledge on how specific fractions of these pollutants can affect treatment processes.
Keywords: Wastewater characterisation; COD; organic matter; nitrogen; phosphorus; fractions; speciation; wastewater treatment; environmental impact